1991
DOI: 10.1093/rheumatology/30.4.301
|View full text |Cite
|
Sign up to set email alerts
|

Aplastic Anaemia in Systemic Lupus Erythematosus: A Cellular Immune Mechanism?

Abstract: Aplastic anaemia is a rare complication of systemic lupus erythematosus (SLE). The mechanism is unclear but is thought to be related to an autoantibody to bone marrow precursors of haematopoiesis. We report a case of SLE related aplastic anaemia in which therapy with methylprednisolone and high dose cyclophosphamide followed by prednisolone and azathioprine resulted in complete clinical and haematological remission. Bone marrow cultures showed inhibition of erythropoiesis when incubated with acute and remissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In contrast to the erythropoietic activity in bone marrow, no shrinkage was observed in the erythroid compartment in the spleen as well as in relative proportions of different stages of erythroid differentiation in AIHA spleens. Opposite effects observed in bone marrow and spleen supports the concept of ‘stress erythropoiesis’ [36,37], where a compensatory surge in spleen erythropoiesis sets in when the bone marrow erythropoietic activity suffers a severe decline. It may be noted that the average total recoveries of cells from spleens and bone-marrows of control and AIHA groups of mice were not significantly different.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In contrast to the erythropoietic activity in bone marrow, no shrinkage was observed in the erythroid compartment in the spleen as well as in relative proportions of different stages of erythroid differentiation in AIHA spleens. Opposite effects observed in bone marrow and spleen supports the concept of ‘stress erythropoiesis’ [36,37], where a compensatory surge in spleen erythropoiesis sets in when the bone marrow erythropoietic activity suffers a severe decline. It may be noted that the average total recoveries of cells from spleens and bone-marrows of control and AIHA groups of mice were not significantly different.…”
Section: Resultsmentioning
confidence: 69%
“…Another factor that may render cells more susceptible to elimination could be the generation of ROS in response to autoantibodies. Presence of autoantibody on bone marrow progenitor cells has been linked to the development of hypoplasia, and even pure red cell aplasia in Systemic lupus erythematosus [36,37]. Like the levels of membrane bound autoantibodies, Erythroblast C stage in bone marrow and reticulocytes and young erythrocytes in blood circulation generate higher levels of ROS and this factor too may contribute to the preferential elimination of these cells in AIHA.…”
Section: Discussionmentioning
confidence: 99%
“…6 Targeted by autoantibodies, the progenitor BM cells lead to various syndromes of haemopoietic failure, such as aplastic anaemia, hypoplasia of myeloid line, amegakaryocytic thrombocytopenia, and the extremely rare pure red cell aplasia (PRCA). [42][43][44][45][46][47][48] The presence of the inhibitory autoantibody is typically related to SLE activity and can be suppressed by successful treatment-that is, by immunosuppression. However, PRCA can occur in the absence of disease activity or even precede the appearance of SLE.…”
Section: Sle: Another Syndrome Of Immune Mediated Haemopoietic Failurementioning
confidence: 99%
“…Bailey et al [8] were also able to demonstrate the presence of an IgG antibody, although noncomplement-dependent, that suppressed proliferation in vitro of bone marrow from normal donors as well as bone marrow obtained from the patient during the recovery phase. Roffe et al [11] showed inhibition of erythropoiesis of bone marrow cultures by acute and remission serum of SLE-associated aplastic anaemia, suggesting that the mechanism for marrow aplasia may be an autoimmune cellular process.…”
Section: ]mentioning
confidence: 99%